Sodium Imbalance in Children with Tuberculous Meningitis: A Cohort Study - Arifianto; Rahayu, Tuty; Banu, Syairah; Fatimatuzzuhroh; Wijaya, Alya Darin (Lembaga Penelitian Universitas YARSI, 2025)
Tuberculous meningitis (TBM) is a severe form of extrapulmonary tuberculosis caused by hematogenous dissemination of Mycobacterium tuberculosis to the meninges. MTB crosses brain protective barriers, creating subependymal collections known as rich foci. Rupture of these foci triggers severe inflammatory responses and meningitis. TBM carrying substantially high rates of morbidity and mortality. Hyponatremia has been linked with adverse clinical outcomes; although the existing evidence in pediatric population remains inconclusive. A retrospective cohort study was conducted at Pasar Rebo General Public Hospital, Jakarta, Indonesia from January 2021 to March 2024. Children aged 0–18 years hospitalized with meningitis and bacteriologically confirmed tuberculosis wereincluded. A total of 26 childrenmet the inclusion criteria. Hyponatremia was present in 76.9% of patients at initial laboratory assessment and persisted in subsequent evaluations despite corrective measures. The risk of hyponatremia was significantly higher among patients receiving diuretic therapy (RR 1.35; 95% CI, 1.061–1.725). Although hyponatremia was not statistically associated with mortality (RR 1.176; 95% CI, 0.979–1.414; p = 1.000), all deaths occurred exclusively in hyponatremic patients, suggesting its potential prognostic relevance.